5 yaş çocukları ve annelerinin paylaşımlı okuma teknikleriyle gerçekleştirdikleri ev merkezli kitap okuma uygulamalarının incelenmesi - ÇELİK, BÜŞRA; UYANIK, GÜLDEN; BİLGİN KÖSE, NAZİFE HÜLYA (My University, 2022)
This study aims to examine the effect of home-based book reading practices performed by 5-year-old children and their mothers with shared reading techniques. For this purpose, the research was designed as a convergent mixed method. The research was modeled as an "experimental model with pretestposttest control group". The study group consists of 28 children aged 5 years and their mothers who were enrolled in a preschool in the Beyoglu district of Istanbul province in the 2020-2021 academic year. 28 children were randomly assigned to the experimental and control groups, and 3 experimental and 1 control group were formed. Information on the demographic characteristics of the study group was collected with the Mother Information Form. Turkish Early Language Development Test (TEDİL), Parent-Child Relationship Scale, Early Literacy Skills Assessment Tool (EOBDA) and Parent Attitude Scale were used as quantitative data collection tools. Audio transcriptions from the experimental process were used as a qualitative data collection tool. As a result of the research, it was concluded that dialogic reading and print referencing made a significant difference in some sub-dimensions of oral language skills and early literacy skills. In addition, it was found that it contributed positively to the mother-child relationship and decreased the authoritarian attitude of the mothers and increased the democratic attitude. The fact that there was no difference in the applications performed without using the technique emphasizes the importance of the ‘interaction’. In the qualitative analysis, it was seen that the mother and child verbal participation at the basic level was realized, but the most qualified verbal participation was in the (1)dialog-based reading and (2)print referencing. Similarly, it was concluded that maternal warmth and maternal sensitivity were seen most in dialogic reading. The participation of the mother and the child affects the child's language and literacy skills and the mother's attitude.
Keywords: 5 years old; mother-child interaction; maternal reading; home literacy environment; shared reading; dialogic reading; print referencing; convergent parallel mixed methods design